Highly palatable diet changes brain glucose metabolism in mice: Prevention (nonpharmacological) / Lifestyle factors (e.g., smoking, etc.). (7th December 2020) - Gehres, Sarah Wehle; da Rocha, Andreia Silva; Rodrigues, Yuri Elias; Peixoto, Guilherme G Schu; Carvalho, Afonso Kopczynski; Carteri, Randhall K; Venturin, Gianina Teribele; Greggio, Samuel; Costa daCosta, Jaderson; Leonardi, Bianca F; Zimmer, Aline R; Souza, Diogo O; et al.
Abstract: Background: Obesity has become a global public health issue and is knowingly associated with several pathological conditions. Epidemiological data indicate it is an important risk factor for the development of neurodegenerative diseases, such as Alzheimer's Disease (AD). However, the pathological mechanisms connecting these two conditions are still elusive. Current evidence points toward glucose metabolism dysregulation, as well as defective insulin signaling and low grade inflammation. Objective: Our main goal was to investigate the effects of a highly palatable diet (HPD) on brain glucose metabolism. Hypothesis: We hypothesized that the obesity induced by the HPD could lead to alterations in brain glucose metabolism similar to those found in AD. Methods: Male C57BL/6J mice (45 days old) were fed with HPD (rich in simple sugars and fat) for four months. They were then examined in vivo via microPET [ 18 F]FDG. Data from images were used to assemble [ 18 F]FDG‐derived brain metabolic networks. A glucose tolerance test (GTT) was also performed to assess peripheral insulin response. Post‐mortem, the brain tissue was used in a high resolution respirometry test to evaluate mitochondrial activity. Results: HPD animals presented increased body weight (HPD= 37.17±4.38g; control= 28.72±1.23g; P<0.0001) and abnormal peripheral tolerance to glucose (peak blood glucose: HPD=421.93±47.13mg/dL; control=323.60±43.83mg/dL P<0.0001). HPD also induced [ 18 F]FDG hypermetabolism in the prefrontal cortex and a hypersynchronicity in the metabolic network, where the hypothalamus appears to be more connected to the hippocampus, thalamus, prefrontal cortex, and striatum. Brain post mortem analysis indicated a less efficient mitochondrial oxidative phosphorylation in the hypothalamus of HPD fed animals as measured by the Respiratory Chain Ratio (HPD=0.640±0.022; control= 0.810±0.012 P<0.001). Conclusion: These preliminary results show that HPD causes peripheral and central disturbances in glucose metabolism, also altering brain mitochondrial activity. Interestingly, in vivo imaging indicates that the prefrontal cortex is highly active and the hypothalamus is unusually connected to other brain regions in these animals.